Effects of metformin and Exenatide on insulin resistance and AMPKα-SIRT1 molecular pathway in PCOS rats - Xin Tao; Lisi Cai; Lei Chen; Shuqi Ge; Xuanying Deng (BMC, 2019)
Abstract Aims This study was designed to evaluate the protective effects of AMPKα and SIRT1 on insulin resistance in PCOS rats, and to illuminate the underlying mechanisms. Methods An in vitro PCOS model was established by DHEA (6 mg/(100 g•d)), and the rats were randomly divided into the metformin group (MF group, n = 11), the exenatide group (EX group, n = 11), the PCOS group (n = 10), and the normal control group (NC group, n = 10). The MF group was administered MF 300 mg/(kg•d) daily. The EX group was subcutaneously injected EX 10μg/(kg•d) daily. After 4 weeks of continuous administration, fasting blood glucose and serum androgen, luteinizing hormone and other biochemical indicators were measured. Western and Real-time PCR were used to determine the expression of AMPKα and SIRT1 in the ovaries of each group. Results After 4 weeks of drug intervention, compared with untreated PCOS group, EX group and MF group had visibly decreased body weight (222.64 ± 16.57, 218.63 ± 13.18 vs 238.30 ± 12.26 g, P = 0.026), fasting blood glucose (7.71 ± 0.72, 8.17 ± 0.54 vs 8.68 ± 0.47 mmol/L, P < 0.01), HOMA-IR (8.26 ± 2.50, 7.44 ± 1.23 vs 12.66 ± 1.44, P < 0.01) and serum androgen (0.09 ± 0.03, 0.09 ± 0.03 vs 0.53 ± 0.41 ng/ml, P < 0.01) and the expressions of AMPKα and SIRT11 were increased progressively (P < 0.05). Conclusions Both metformin and exenatide can improve the reproductive and endocrine functions of rats with PCOS via the AMPKα-SIRT1 pathway, which may be the molecular mechanism for IR in PCOS and could possibly serve as a therapeutic target.